2015
DOI: 10.5812/jjm.8(5)2015.19180
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Epidemiology of Acinetobacter calcoaceticus baumannii Complex Strains Spread at Nemazee Hospital of Shiraz, Iran

Abstract: BackgroundAcinetobacter calcoaceticus baumannii (ACB) complex are Gram-negative opportunistic bacteria with low virulence properties. Their resistance to antibiotics has become a matter of concern in hospital infections.ObjectivesThe present study aimed to determine the prevalence and antimicrobial susceptibility of ACB isolates collected from the Nemazee hospital of Shiraz. In addition, Pulsed Field Gel Electrophoresis (PFGE) was used to determine the genetic patterns of these strains.Patients and MethodsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In recent years, the Acinetobacter spp. isolation rate in our region, especially at Nemazee Hospital, has been remarkable (25,27) Etiological agents of septicemia have varied in previous reports from Iranian studies. In agreement with our study, Gheibi et al from Urmia reported Gram positive cocci, especially CoNS, as the most prevalent agents of neonatal septicemia (19).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In recent years, the Acinetobacter spp. isolation rate in our region, especially at Nemazee Hospital, has been remarkable (25,27) Etiological agents of septicemia have varied in previous reports from Iranian studies. In agreement with our study, Gheibi et al from Urmia reported Gram positive cocci, especially CoNS, as the most prevalent agents of neonatal septicemia (19).…”
Section: Discussionmentioning
confidence: 84%
“…Acinetobacter spp. has become a growing cause of nosocomial infections and has been known to cause different kinds of opportunistic infections (25,26). In recent years, the Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter baumannii is one of the main causes of nosocomial infections in the recent years (18). Acinetobacter baumannii is one of the most problematic organisms currently responsible for nosocomial infections, especially in intensive care units (ICUs) (19).…”
Section: Discussionmentioning
confidence: 99%
“…42 Nowadays, a majority of A. baumannii species have become resistant to third and fourth generation cephalosporins, and the reason is their ability to produce ESBL which leads to cephalosporin resistance. 42,43 Generally, carbapenems are identified as agent of choice to treat A. baumannii infections, 42 but treating it has become difficult due to the occurrence of carbapenemresistant species including multi drug resistant (MDR) and extensively drug resistant (XDR). [42][43][44][45] In Gao et al study, 75% of isolated species were CRAB and the rate of was highest in patients with pneumonia.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…42,43 Generally, carbapenems are identified as agent of choice to treat A. baumannii infections, 42 but treating it has become difficult due to the occurrence of carbapenemresistant species including multi drug resistant (MDR) and extensively drug resistant (XDR). [42][43][44][45] In Gao et al study, 75% of isolated species were CRAB and the rate of was highest in patients with pneumonia. 36 In Kim et al study, 82.4% of A. baumannii species and 33.3% of Acinetobacter Lwoffii species were carbapenem resistant.…”
Section: Prevention and Treatmentmentioning
confidence: 99%